A Comparison between the Effects of Albendazole and Mebendazole on the Enzymatic Activity of Excretory / Secretory Products of Echinococcus granulosus Protoscoleces in Vitro - ADNANI SADATI, Seyed Jafar (Iran J Public Health, 2016)
BACKGROUND: Hydatid cysts are formed in human body can be treated clinically by surgery or drugs such as albendazole (ABZ) and mebendazole (MBZ). The purpose of this study was comparing the effects of ABZ and MBZ on glutathione-S-transferase, alkaline phosphatase and protease enzymes activities in protoscoleces of hydatid cyst. METHODS: The culture supernatants containing the parasite Excretory / Secretory (E/S) products were collected every 12 h for 72 h. The E/S products of treated samples with 1μg/ml ABZ and MBZ and the control one were collected and after centrifugation then protein concentrations were measured according to Bradford method. GST, ALP and protease activities of E/S products were assessed photometrically. RESULTS: The mean of GST specific activity level in treated protoscoleces with ABZ and MBZ and in control group were obtained 69.44, 132.83 and 225.47U/mg/protein/ml respectively. The mean ALP activity level in treated protoscoleces with ABZ and MBZ and in control group were detected 19.22, 22.27 and 27.85 U/mg/protein/ml respectively. The protease activity level in treated protoscoleces with ABZ and MBZ were not detected. While the mean of protease activity level in control group was 7.61U/mg/proteins. Statistical analysis showed the significant difference between protein concentrations, the specific activities of GST, ALP and protease enzymes in treated protoscoleces in comparison with control group (P<0.05). Also, the significant difference were seen between specific activities of GST and ALP enzymes in treated protoscoleces with ABZ in comparison with treated group with MBZ (P<0.05). CONCLUSION: ABZ is more effective on the enzymes activities (GST and ALP) as compared with MBZ.